PENGGUNAAN MULSA TERHADAP PERTAMBAHAN TINGGI TANAMAN GORAKA MERAH (Zingiber officinale, Rosc.) DI KECAMATAN TOMBARIRI - Ruitang, Rivandy R.R.; Purbopuspito, Joko; Titah, Tilda (Soil and Environment Journal, 2022)
Mulches on the Height Growth of Red Goraka (Red Ginger, Zingiber officinale, Rosc.) Plants in Tombariri District This study documented the effect of using plastic mulch and litter mulch and the recommended dosage of PT Bintang Toejoe fertilizer on the growth of the Goraka Merah (Red Ginger) plants in Tombariri District. The study was conducted on a smallholder coconut plantation by documenting the soil profile, measuring the height (cm) of the Goraka plants in 6 treatments and 4 replicates, which was carried out every week for three months starting at the beginning Goraka growths of 21 clumps/beds in total of 24 beds. The topsoil in the Tambala study area has a clayed loam texture with a very dark brown soil color which is relatively fertile compared to its subsoil. In the beds without fertilizer, the highest growth of Goraka Merah was seen in the mulch treatment compared to the no-mulch treatment. The growth of the Red Goraka with the recommended dose of fertilizer treatment was better than the growth without fertilizer. While in fertilized conditions, the growth of Goraka with plastic mulch, litter mulch and control treatments were similar in the first three months of Goraka Red Ginger growth observations.